Dynamical behaviors of optical solitons, and Jacobi elliptic wave solutions of fractional chiral (2+1) dimensional NLSE in physics - Roshid, Mamunur; Bashar, Habibul; Rezapour, Shahram; İnç, Mustafa (Elsevier, 2025)
Various complex nonlinear evolution equations are used to illustrate the inner characteristics of various complex processes that occur in real-life events. In this framework, we use extended Jacobian elliptic function expansion (JEFET) and extended hyperbolic function techniques (EHFT) to analyze optical soliton solutions (SSs) of fractional chiral (2 + 1) dimensional nonlinear Schrodinger's equation ((2 + 1)-D CNLSE) in field of physics and in the field of fluid sciences. The suggested methods provide insights into optical soliton in a variety of technical fields, including quantum mechanics, plasma physics, nonlinear optics, and optical communications. While nonlinearity produces distortions, dispersion causes signals to disperse and deteriorate over distance. These methods allow us to produce some optical soliton solutions that may be analytically expressed in terms of rational, hyperbolic, trigonometric, and elliptic functions. Double periodic wave (PW), PW with lump wave SSs, breather wave with PW, various kinky PW, periodic breather wave by using the extended JEFET, and double PW, kink-PW, periodic breather wave, double PW patterns by using the EHFT are the numerical forms of the obtained solution that are studied with three and two-dimensional diagrams in figures 1 through 10. We demonstrate the impact of truncated M-fractional parameters (MFP) for [s = 0.1,0.5,0.9] on a two-dimensional graph. The gathered results could help to clarify and better understand the physical properties of waves traveling through a dispersive material. As a result, the previously discussed applied techniques may be a useful tool for producing distinct, accurate SSs for a variety of applications, which are essential to engineering, nonlinear optics, and fluid.
Keywords: (2+1)-D CNLSE; Extended jacobian elliptic function expansion; Extended hyperbolic function techniques; Truncated M-fraction; Nonlinear optics etc